Kreativitas Guru Dalam Memilih Strategi Pembelajaran Yang Efektif Untuk Persiapan Menghadapi Kurikulum Nasional - Muhammad Nizar Ibrahim; Reynitha Putri Bilqhis (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
In facing the dynamics of the national curriculum which continues to develop, it is important to understand the role of teacher creativity in choosing effective learning strategies. This research aims to explore and understand how teacher creativity can be used in choosing effective learning strategies to prepare for the National Curriculum. Through a qualitative literature study approach, this research investigates various text sources, journals, and related research to gain in-depth insight into how teachers use their creativity in designing interesting and meaningful learning experiences for students. The findings show that teacher creativity plays an important role in responding to the demands of the continuously developing national curriculum, which demands adaptation and innovation in learning methods. Creative teachers can choose and adapt various learning strategies, such as project-based learning, group discussions, and technology-based approaches, according to student needs and the learning objectives set in the curriculum. By utilizing their creativity, teachers can create a learning environment that motivates, inspires, and produces optimal learning outcomes. The implications of this research highlight the importance of providing support and training to teachers to develop their creative skills in selecting learning strategies that suit the changing national curriculum context and diverse student needs